The Double-Faceted Role of Leucine-Rich Repeat Kinase 2 in the Immunopathogenesis of Parkinson’s Disease - Zhang, Mengfei; Li, Chaoyi; Ren, Jie; Wang, Huakun; Yi, Fang; Wu, Junjiao; Tang, Yu (Frontiers in Aging Neuroscience, 2022)
Leucine-rich repeat kinase 2 (LRRK2) is one of the most common causative genes in Parkinson's disease (PD). The complex structure of this multiple domains’ protein determines its versatile functions in multiple physiological processes, including migration, autophagy, phagocytosis, and mitochondrial function, among others. Mounting studies have also demonstrated the role of LRRK2 in mediating neuroinflammation, the prominent hallmark of PD, and intricate functions in immune cells, such as microglia, macrophages, and astrocytes. Of those, microglia were extensively studied in PD, which serves as the resident immune cell of the central nervous system that is rapidly activated upon neuronal injury and pathogenic insult. Moreover, the activation and function of immune cells can be achieved by modulating their intracellular metabolic profiles, in which LRRK2 plays an emerging role. Here, we provide an updated review focusing on the double-faceted role of LRRK2 in regulating various cellular physiology and immune functions especially in microglia. Moreover, we will summarize the latest discovery of the three-dimensional structure of LRRK2, as well as the function and dysfunction of LRRK2 in immune cell-related pathways.